Strengthening Intention To Stay In Era Of Industry 4.0: Role Of Employee Skills And Mental Health In The Digital Work - Wiwit Amalia; Ali; Anna Widiastuti (LP2M IAIN Palopo, 2026)
This study aims to analyze strategies for strengthening employee intention to stay in the Industry 4.0 era, focusing on the roles of employee skills and mental health, with digital transformation serving as a mediating variable at PT Safelock Medical. The methodology employs an explanatory quantitative design involving 125 employees with a minimum of one year of tenure who utilize the 'Akurat Online' system. Sampling was conducted using an incidental sampling technique, and data were analyzed using the SEM-PLS method via SmartPLS 4.0 software. The findings reveal that both employee skills and mental health have a positive and significant direct impact on the intention to stay. Furthermore, the study finds that mental health exerts a stronger influence on digital transformation compared to employee skills. However, hypothesis testing indicates that digital transformation does not significantly influence the intention to stay within this specific model. From a practical standpoint, PT Safelock Medical is advised to prioritize well-being programs to ensure the mental health resilience of employees in navigating the demands of a digital work environment. Keywords:Intention to Stay; Employee Skills; Mental Health; Digital Transformation